Knowledge and challenges associated with Management of type 2 Diabetes Mellitus among Adults aged 45-60 years attending Diabetic Clinic at Buwambo Health Centre IV. A Cross-sectional Study. - Kabanyana, Florence (Student’s Journal of Health Research Africa, 2022)
Background: Type 2 diabetes mellitus is a type of diabetes mellitus that is very prevalent in Uganda and affects a wide percentage of the adult population. Much as there have been successive. Interventions in the prevention and control of this non-communicable disease, it is still increasing annually. Methodology: This was a cross-sectional study conducted to assess the challenges associated with the management of type 2 diabetes mellitus among adults aged 45-60 years attending the diabetic clinic at Buwambo Health Centre IV and the researcher sought to determine the knowledge, lifestyle factors, and health facility-related factors associated with the management of type 2 diabetes mellitus among the same population. Results: Study findings revealed that males were the majority 65% and stayed in a rural residence 69%. Most of the respondents had sufficient knowledge of diabetes mellitus. More than 80% knew the definition, types, signs, and causes of diabetes. The majority of respondents said there was general readiness of facilities to handle diabetes but the health workers needed more training. Conclusion: The study findings indicated that health facilities are generally ready to manage diabetes mellitus with enough medications and fairly well-trained personnel to manage the disease Recommendation: There is a need for the government to therefore prioritize the non-communicable disease treatment and prevention budget, for the health facilities to develop better organizational structures in diabetic clinics and proper stock management. All these will help to reduce the diabetes disease burden in the country at large.